(3GdeYde aj TQM cJGH eSde (B( (3GdUMjM (B)s - (3CHh YHO Gddg eMeO Hf Ydj GdeGRQi GdeGdcjs; (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf,J (B261 (3g` s
(3ChdgG (B:s
(3GdMeO ddg efRd GdCMcGe gPG cJGH bUO ajg Edi JYdjb eG LQi ai eLGdS Gdabjg GdeGRQi QVi Gddg Yfg MjHf GdbQGAI Ydjg GdcJGH eSde s
(3BNQgG (B:s
(3ef TQM cJGH GdJaSjQ (B: (3hhbY ai fSNI GHf eGgGf ai ESfGO gPG GdMOjK (B: (3YHO GdMejO , ecGf YHO GdeLjO hGdChd GdUhGH Ef TGA Gddg YR hLd ced LejY cJGH GdeYde s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs